Assisting Teachers Using AI Auto-Generate as a Formative Assessment Tool on EFL Students’ Reading Comprehension in the Digital Era - Cahyanto, Iman; Sutrisno, Andy (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the use of AI as a formative evaluation tool for English as a Foreign Language (EFL) students' reading comprehension in the digital age. AI is a crucial technology in education that enhances teaching and learning processes. Formative assessment helps students develop their abilities and skills, while summative evaluations measure performance. AI can be used to test students' reading comprehension using smartphone apps like Novel Applications, Sports and Podcasts, and Netflix. The research aims to help teachers use AI auto-generation as a formative evaluation tool, outlining its benefits and drawbacks. It also suggests that readers should use Formative Apps to measure students' reading comprehension in the digital age to assist teachers.